The distribution of households consumption-expenditure budget shares - Matteo Barigozzi; Lucia Alessi; Marco Capasso; Giorgio Fagiolo (European Central Bank (ECB), 2009)
This paper explores the statistical properties of house-hold consumption-expenditure budget share distributions —defined as the share of household total expenditure spent for purchasing a specific category of commodities— for a large sample of Italian households in the period 1989-2004. We find that household budget share distributions are fairly stable over time for each specific category, but profoundly heterogeneous across commodity categories. We then derive a para-metric density that is able to satisfactorily characterize household budget share distributions and: (i) is consistent with the observed statistical properties of the underlying levels of household consumption-expenditure distributions; (ii) can accommodate the observed across-category heterogeneity in household budget share distributions. Finally, we taxonomize commodity categories according to the estimated parameters of the proposed density. We show that the resulting classification is consistent with the traditional economic scheme that labels commodities as necessary, luxury or inferior.
Keywords: D3; D12; C12; 330; Budget Shares; Household Consumption Expenditure; Sum of Log-Normal Distributions; Privater Konsum; Haushaltsstatistik; Statistische Verteilung; Klassifikation; Italien